Harmonizing wisdom in social business enterprises - Mhd. Sarif, Suhaimi (2015)
The purpose of this keynote is to expose staff and students of Victoria International College to the importance of generating wisdom from the knowledge that they gained throughout their studies. The industry needs practical wisdom to operationalize business activities and ventures. Without wisdom, industry will make mistakes. Mistakes can cause the industry to go backward or vanish entirely. The key ideas of the study are generated from the feedback of students and stakeholders. The findings from this talk can be shared with others.